Effect of 900 MHz Electromagnetic Radiation on the Induction of ROS in Human Peripheral Blood Mononuclear Cells - Kazemi, E. (J Biomed Phys Eng, 2015)
BACKGROUND: Despite numerous studies over a decade, it still remains controversial about the biological effects of RF EMF emitted by mobile phone telephony. OBJECTIVE: Here we investigated the effect of 900 MHz GSM on the induction of oxidative stress and the level of intracellular reactive oxygen species (ROS) in human mononuclear cells, monocytes and lymphocytes as defence system cells. METHOD: 6 ml Peripheral Blood samples were obtained from 13 healthy volunteers (21-30 year-old). Each sample was devided into 2 groups: one was exposed RF radiation emitted from a mobile phone simulator for 2 hour and the other used as control group which was not exposed to any fields. After that, mononuclear cells were isolated from peripheral blood by density gradient centrifugation in Ficoll-Paque. The intracellular ROS content in monocytes and lymphocytes was measured by the CM-H2DCFDA fluorescence probe using flowcytometry technique. RESULTS: Our results showed significant increase in  ROS production after exposure in population rich in monocytes. This effect was not significant in population rich in lymphocytes in comparison with non exposed cells. CONCLUSION: The results obtained in this study clearly showed the oxidative stress induction capability of RF electromagnetic field in the portion of PBMCs mostly in monocytes, like the case of exposure to micro organisms, although the advantages or disadvantages of this effect should be evaluated.